Investigating the association of pan-immune-inflammation value, systemic immune-inflammation index, and neutrophil-to-lymphocyte ratio with pain in Parkinson’s disease - Pan, Heyue; Wang, Xiaohua; Zhang, Xiulin; Shi, Xiangsong; Sun, Taipeng; Xu, Jianyang; Wang, Shouyong (Frontiers in Neurology, 2025)
ObjectiveTo explore the relationship between novel composite inflammatory markers—pan-immune-inflammation value (PIV), systemic immune-inflammation index (SII), and neutrophil-to-lymphocyte ratio (NLR)—and the presence of pain in patients with Parkinson’s disease (PD).MethodsA total of 150 PD patients who attended the outpatient or inpatient departments of the Second Clinical College of Xuzhou Medical University (Huai’an Third People’s Hospital) between September 2020 and December 2023 were enrolled as the PD group. An additional 150 age- and sex-matched healthy individuals undergoing routine physical examinations were selected as the healthy control (HC) group. The King’s Parkinson’s Disease Pain Scale (KPPS), Hoehn-Yahr (H-Y) staging, Unified Parkinson’s Disease Rating Scale part III (UPDRS-III), Hamilton Depression Rating Scale-24 (HAMD-24), and Hamilton Anxiety Rating Scale (HAMA) were used to assess pain, disease severity, motor symptoms, depression, and anxiety in PD patients. Demographic and laboratory data were collected for all participants. Based on KPPS scores, PD patients were subdivided into those with pain (PDP group) and those without pain (nPDP group). Intergroup differences were compared, and the associations of PIV, SII, and NLR with pain in PD were analyzed.ResultsAmong the 150 PD patients, 79 (52.7%) reported pain, with a mean KPPS score of 10.81 ± 8.67. Compared to the HC group, PD patients exhibited significantly elevated levels of PIV, SII/100, and NLR, and significantly lower platelet and lymphocyte counts (p < 0.05). In subgroup analysis, PIV, SII/100, H-Y stage, UPDRS-III, and HAMD-24 scores were significantly higher in the PDP group than in the nPDP group (p < 0.05). KPPS scores were positively correlated with PIV, H-Y stage, UPDRS-III, and HAMD-24 scores, but not with SII/100 or NLR.ConclusionInflammatory dysregulation is present in PD patients. Compared with the nPDP group, patients in the PDP group showed significantly higher levels of PIV and SII/100, as well as greater disease severity (H-Y stage, UPDRS-III) and more pronounced depressive symptoms (HAMD-24) (p < 0.05). Moreover, KPPS scores in PD patients were not only associated with PIV but also positively correlated with disease stage, motor function impairment, overall disease severity, anxiety, and depression.